MYOCARDIAL INFARCTION IN PATIENTS WITHOUT DIABETES THE IMPORTANCE OF HEMOGLOBIN A1C - Cambay, Zafer (Parlar Scientific Publications (P S P), 2019)
In this study, non-diabetic myocardial infarction with ST elevation, representing acute myocardial infarction and non-diabetic patients with no history of myocardial infarction have compared. Subjects included 180 non-diabetic patients who suffered a myocardial infarction with ST elevation, representing acute myocardial infarction (group 1), 180 non-diabetic patients with no history of myocardial infarction, who were scheduled for coronary artery bypass graft surgery, representing coroner artery disease (group 2), and 100 healthy controls (group 3). Groups 1 and 2 had higher levels of hypertension and HbA(1c), low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and fasting plasma glucose (FPG) levels compared to those of group 3. Groups 1 and 2 had similar FPG and HbA(1c) levels. FPG and HbA(1c) levels of groups 1 and 2 were significantly higher than those in the control group (P = 0.001, P = 0.041 and P = 0.001, respectively). Statically, there was not observed any difference between patients with non-diabetic myocardial infarction and non-diabetic patients with history of myocardial infarction. Prediabetes and diabetes were frequently seen in both groups, but most patients were unaware. Detecting prediabetes and diabetes early is important. HbA(1c) represents a good choice for screening and follow-up evaluations of prediabetes and diabetes in patients with coroner artery disease.
Keywords: Myocardial infarction; hemoglobin A1c; prediabetes; diabetes